Low-dose short synacthen test with salivary cortisol in patients with suspected central adrenal insufficiency. Issue 9 (20th September 2021) - Ceccato, Filippo; Selmin, Elisa; Antonelli, Giorgia; Barbot, Mattia; Daniele, Andrea; Boscaro, Marco; Plebani, Mario; Scaroni, Carla
Abstract : Context: The low-dose short synacthen test (LDSST) is recommended for patients with suspected central adrenal insufficiency (AI) if their basal serum cortisol (F) levels are not indicative of an intact hypothalamic–pituitary–adrenal (HPA) axis. Objective: To evaluate diagnostic threshold for salivary F before and 30 min after administering 1 μg of synacthen, performed before 09:30 h. Design: A cross-sectional study from 2014 to 2020. Setting: A tertiary referral university hospital. Patients: In this study, 174 patients with suspected AI, 37 with central AI and 137 adrenal sufficient (AS), were included. Main outcome measure: The diagnostic accuracy (sensitivity (SE), specificity (SP)) of serum and salivary F levels measured, respectively, by chemiluminescence immunoassay and liquid chromatography-tandem mass spectrometry. Results: Low basal serum or salivary F levels could predict AI. For the LDSST, the best ROC-calculated threshold for serum F to differentiate AI from AS was 427 nmol/L (SE 79%, SP 89%), serum F > 500 nmol/L reached SP 100%. A salivary F peak > 12.1 nmol/L after administering synacthen reached SE 95% and SP 84% for diagnosing central AI, indicating a conclusive reduction in the likelihood of AI. This ROC-calculated threshold for salivary F was similar to the 2.5th percentile of patients with a normal HPA axis, so it was considered sufficient to exclude AI. Considering AS those patients with salivary F > 12.1 nmol/L after LDSST, we could avoid unnecessary glucocorticoid treatment: 99/150 subjects (66%) had an inadequate serum F peak after synacthen, but salivary F was >12.1 nmol/L in 79 cases, who could, therefore, be considered AS. Conclusions: Salivary F levels > 12.1 nmol/L after synacthen administration can indicate an intact HPA axis in patients with an incomplete serum F response, avoiding the need to start glucocorticoid replacement treatment.